2023
DOI: 10.21203/rs.3.rs-2550306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of ultrasound in etiological diagnosis of carpal tunnel syndrome caused by persistent median artery

Abstract: Objectives: To explore the value of ultrasound in the etiological diagnosis of carpal tunnel syndrome(CTS) caused by persistent median artery(PMA) and the advantage of ultrasound in the diagnosis of carpal tunnel syndrome combined with persistent median artery. Methods: From May 2017 to May 2022,5 patients with persistent median artery who underwent bilateral carpal tunnel ultrasound examination in our hospital were enrolled in this study. All patients underwent bilateral carpal tunnel ultrasound examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The decrease in iron storage is closely related to malnutrition, digestive system surgery, and chronic blood loss, and iron metabolism disorder is mainly related to chronic inflammation. 31 The findings of this study further demonstrate that CRP is a significant influencing factor for CRA in patients with normal serum iron in lung cancer, which means that the inflammatory state represented by CRP can affect CRA. Studies have confirmed that when the body is in an inflammatory state, the release of inflammatory factors can be regarded as an important cause of CRA, 32 which mainly shows that proinflammatory cytokines can promote the secretion of inflammatory factors, such as interleukin-1 (IL-1), interleukin-6 (IL-6), interferon, and tumor necrosis factor (TNF), etc., which can not only inhibit the production of red blood cells but also promote their apoptosis, thus leading to inflammatory anemia or chronic disease.…”
Section: Discussionsupporting
confidence: 66%
“…The decrease in iron storage is closely related to malnutrition, digestive system surgery, and chronic blood loss, and iron metabolism disorder is mainly related to chronic inflammation. 31 The findings of this study further demonstrate that CRP is a significant influencing factor for CRA in patients with normal serum iron in lung cancer, which means that the inflammatory state represented by CRP can affect CRA. Studies have confirmed that when the body is in an inflammatory state, the release of inflammatory factors can be regarded as an important cause of CRA, 32 which mainly shows that proinflammatory cytokines can promote the secretion of inflammatory factors, such as interleukin-1 (IL-1), interleukin-6 (IL-6), interferon, and tumor necrosis factor (TNF), etc., which can not only inhibit the production of red blood cells but also promote their apoptosis, thus leading to inflammatory anemia or chronic disease.…”
Section: Discussionsupporting
confidence: 66%